Reassessing the Links with Health and the Welfare State - St John, Susan (Victoria University of Wellington Law Review, 2004)
The author provides a summary of an Accident Compensation conference. Two main ACC themes are provided: the distinction between disability from accident and disability from illness, and the boundary between work and non-work injuries. The author reminds the reader of the social contract found in the original Woodhouse Report. She argues that she does not see the welfare state withering away – rather, the need for it, and its social insurance aspects, become even more crucial in light of new complex risks.